2007
DOI: 10.1103/physrevc.76.064303
|View full text |Cite
|
Sign up to set email alerts
|

E(5) and X(5) shape phase transitions within a Skyrme-Hartree-Fock + BCS approach

Abstract: Self-consistent Skyrme-Hartree-Fock plus BCS calculations are performed to generate potential energy curves (PECs) in various chains of Pd, Xe, Ba, Nd, Sm, Gd, and Dy isotopes. The evolution of shapes with the number of nucleons is studied in a search for signatures of E(5) and X(5) critical point symmetries. It is shown that the energy barriers in the PECs are determined to a large extent by the treatment of the pairing correlations.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
66
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(80 citation statements)
references
References 38 publications
13
66
0
1
Order By: Relevance
“…A comparison with similar results obtained in Ref. [19] with the parametrization SLy4 of the Skyrme force [21] plus a zero range pairing [22] will also be considered.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…A comparison with similar results obtained in Ref. [19] with the parametrization SLy4 of the Skyrme force [21] plus a zero range pairing [22] will also be considered.…”
Section: Introductionmentioning
confidence: 99%
“…Different combinations of mean-field and pairing treatments were also considered in Ref. [19]. As a result of this study, it was found that the energy of the spherical barriers strongly depend on the details of the calculations, especially on the pairing force.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations